Development of Fern Media to Increase the Active Learning of Class II MI Nurul Falah Brati Students in Material Places of Living Creatures Learning Content in Natural Sciences - Fitriana, Vera; S, Imam Maulana; Yunianto, Rifan; Masfuah, Siti; Suryani, Fitri Budi; Najikhah, Fatikhatun (Journal of Learning Improvement and Lesson Study, 2023)
The background of this research is the low learning activity of class II students of MI Nurul Falah Brati on Material Places of Living Creatures Living Science Learning Content with a score of 50% which is due to limited learning media. The purpose of this study was to measure the increase in class II student learning activeness by using Pakis media. The type of research used isResearch & Development (R&D) with the ADDIE model on stage Development. The research subjects used were class II students at MI Nurul Falah Brati, totaling four students. The data analysis technique used is qualitative and quantitative data analysis. the data collection techniques used were interviews, validity questionnaires, observation, and limited scale trial questionnaires. The results of media expert validation obtained an average score of 96% in the "Very feasible" category. In the observation of learning activity, a score of 88.875 was obtained in the "very decent" category. In the limited scale trial questionnaire, an average score of 91.225% was obtained in the "Very feasible" category. The pretest and posttest results increased by 1.36 with moderate criteria. So it can be concluded that the use of PAKIS media can increase the learning activity of class II MI Nurul Falah Brati students.